2020
DOI: 10.1105/tpc.19.00869
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Flippases Cooperate with ARF GTPase Exchange Factors to Regulate the Trafficking and Polarity of PIN Auxin Transporters

Abstract: Cell polarity is a fundamental feature of all multicellular organisms. PIN auxin transporters are important cell polarity markers that play crucial roles in a plethora of developmental processes in plants.Here, to identify components involved in cell polarity establishment and maintenance in plants, we carried out a forward genetic screening of PIN2:PIN1-HA;pin2 Arabidopsis thaliana plants, which ectopically express predominantly basally localized PIN1 in root epidermal cells, leading to agravitropic root grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 124 publications
2
68
0
Order By: Relevance
“…Previous studies have shown that ALA3 participates in many crucial physiological activities via multiple mechanisms, including root and pollen tube growth (Poulsen et al, 2008;McDowell et al, 2013;Zhang et al, 2020), trichome development (Zhang and Oppenheimer, 2009), and resistance to pathogens (Underwood et al, 2017). For example, in Arabidopsis root and tobacco leaf cells, ALA3 was reported to be localized mainly in the Golgi apparatus and only partially in the TGN/EE, and loss of function of ALA3 led to a defect in the production of secretory vesicles in root peripheral columella cells, which thereby inhibited root growth (Poulsen et al, 2008).The latest research has reported that ALA3, which is located mainly in the Glogi, TGN/EE, and PM, functions together with the ARF GTPase exchange factors (GNOM and BIG3) in regulating PIN polarity, trafficking, and auxin-mediated development (Zhang et al, 2020). In addition, it was recently shown that loss of ALA3 function had a negative impact on the cycling of the defense protein PENETRATION3 between the PM and TGN/EE and subsequently affected plant immune responses against powdery mildews (Underwood et al, 2017).…”
Section: Ala3 Is a Key Regulator Of Ps Distribution And The Polarizedmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ALA3 participates in many crucial physiological activities via multiple mechanisms, including root and pollen tube growth (Poulsen et al, 2008;McDowell et al, 2013;Zhang et al, 2020), trichome development (Zhang and Oppenheimer, 2009), and resistance to pathogens (Underwood et al, 2017). For example, in Arabidopsis root and tobacco leaf cells, ALA3 was reported to be localized mainly in the Golgi apparatus and only partially in the TGN/EE, and loss of function of ALA3 led to a defect in the production of secretory vesicles in root peripheral columella cells, which thereby inhibited root growth (Poulsen et al, 2008).The latest research has reported that ALA3, which is located mainly in the Glogi, TGN/EE, and PM, functions together with the ARF GTPase exchange factors (GNOM and BIG3) in regulating PIN polarity, trafficking, and auxin-mediated development (Zhang et al, 2020). In addition, it was recently shown that loss of ALA3 function had a negative impact on the cycling of the defense protein PENETRATION3 between the PM and TGN/EE and subsequently affected plant immune responses against powdery mildews (Underwood et al, 2017).…”
Section: Ala3 Is a Key Regulator Of Ps Distribution And The Polarizedmentioning
confidence: 99%
“…The Arabidopsis P4-ATPase family consists of 12 members, termed aminophospholipid ATPases 1-12 (ALA1-ALA12). In recent years, progress in the research on flippases in plants has shown that P4-ATPases have pleiotropic effects on physiological functions, including plant growth and development, reproduction, and adaptation to biotic and abiotic stress (Gomès et al, 2000;Poulsen et al, 2008;Zhang and Oppenheimer, 2009;McDowell et al, 2013;Poulsen et al, 2015;Botella et al, 2016;Guo et al, 2017;Niu et al, 2017;Underwood et al, 2017;Zhang et al, 2020). However, whether ALAs are involved in the establishment of the asymmetric distribution of PS in pollen tubes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To test whether POME could be used to determine which side of the interphase between two adjacent cells a protein resides, we quantified the localization of BRXL2 and the transmembrane protein PIN2 in Arabidopsis roots. BRXL2 has been reported to localize rootward in roots (Marhava et al, 2020) and PIN2 to localize shootward in root epidermis cells (Wisniewska et al, 2006). We quantified the pixel intensity at multiple "rings" surrounding the plasma membrane to ascertain whether a polarized protein is enriched in either outer or inner rings of a particular cell.…”
Section: Applications Of Pome In Other Developmental Contextsmentioning
confidence: 99%
“…Many other proteins exhibiting polarized distributions in plants have been identified over the past decade, but our understanding of the mechanisms that control their distribution is still in its infancy (Denninger et al, 2019;Dong et al, 2009;Houbaert et al, 2018;Marhava et al, 2018;Scacchi et al, 2009;Tan et al, 2020;van Dop et al, 2020;Yoshida et al, 2019;Zhang et al, 2020;Zourelidou et al, 2009). Quantifying the distribution of polar proteins in time and space is a necessary first step in understanding how cell polarity is formed and coordinated with neighboring or daughter cells.…”
Section: Introductionmentioning
confidence: 99%
“…The polar localization of the PIN proteins at the PM requires post-translational modification of PIN proteins and membrane trafficking (Zwiewka et al, 2019;Zhang et al, 2020). For instance, in the root vascular tissues, PIN1 proteins are reversibly accumulated in endosomes and depleted from the PM upon treatment, when seedlings are treated with the vesicle transport inhibitor brefeldin A (BFA) (Geldner et al, 2003;Zwiewka et al, 2019).…”
Section: Introductionmentioning
confidence: 99%